European Industrial Policy – Tapping the Full Growth Potential of the EU - Erik Berglof (Intereconomics, 2016)
Europe, like many of the world's advanced economies, is facing a fundamental growth challenge. Growth has slowed in the wake of the global financial crisis, as investment has decreased and the legacy of non-performing loans and uncertainty about the institutional arrangements established in response to the crisis are likely to be with us for years. However, the evidence suggests that this slowdown started before the crisis, as improvements in productivity did not come at the same pace as in the past.
Keywords: 330